2015
DOI: 10.1111/1471-0528.13332
|View full text |Cite
|
Sign up to set email alerts
|

The levator ani muscle during pregnancy and major levator ani muscle defects diagnosed postpartum: a three‐ and four‐dimensional transperineal ultrasound study

Abstract: Objective To investigate associations between levator hiatus area and levator ani muscle function during pregnancy and major levator ani muscle defects postpartum.Design Observational prospective cohort study.Setting University hospital, Norway.Sample A cohort of 234 nulliparous women at 21 and 37 weeks of gestation, and at 6 weeks postpartum.Methods Ultrasound measurements of the levator hiatus at rest, during pelvic floor muscle contraction, and during the Valsalva manoeuvre were taken at 21 and 37 weeks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 46 publications
2
45
0
1
Order By: Relevance
“…However, as studies have shown, forceps delivery appears to be a risk factor for a higher grade of pelvic floor trauma. Additionally, more potential risk factors such as age or fetal head circumference have been identified to be linked with more severe damage to the levator ani . We only considered these parameters to describe the patient collective.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, as studies have shown, forceps delivery appears to be a risk factor for a higher grade of pelvic floor trauma. Additionally, more potential risk factors such as age or fetal head circumference have been identified to be linked with more severe damage to the levator ani . We only considered these parameters to describe the patient collective.…”
Section: Resultsmentioning
confidence: 99%
“…We only considered these parameters to describe the patient collective. On the other hand, it is possible that the extent of injury is mainly attributable to individual tissue character rather than to the factors mentioned above . Future studies will have to consider the influence of the named further variables.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrasonic sensors are used for imaging in various fields of science and engineering, ranging from fetal scanners [1][2][3][4][5] to non-destructive testing and evaluation of nuclear power stations [6][7][8]. Ultrasound transducers are the components which generate and detect sound waves, converting electrical energy to mechanical energy (and vice versa) through vibrations induced on the transducer [9].…”
Section: Introductionmentioning
confidence: 99%